Obtaining bakery products from partial replacement of wheat flour by pupunha flour (Research, Society and Development, 2023)
The objective of this work was to obtain bakery products from the partial replacement of wheat flour by whole peach palm flour. The flour was obtained by removing the seeds from the fruits, cooking them, drying and grinding them. After defining the formulations with the partial replacement of wheat flour by peach palm flour, the products were characterized in terms of water activity (Aw), moisture, ash, lipids, proteins, fibers, total carotenoids, carbohydrates, energy value and acceptance sensory. Peach palm flour, with a water activity of 0.275, can be classified as a food with low water activity and, therefore, stable for a long period of time. In addition, it has considerable levels of proteins (5.83%), lipids (19.45%), fibers (6.60%) and total carotenoids (13.01 mg/100g), which makes it of great interest. Regarding the results of the physical-chemical characterization of the prepared bakery products, highlighted in the cake, cookie and bread obtained the contents of carbohydrates (60.49%, 59.38% and 48.70%), proteins (10.28%, 10.141% and 12.90%) and lipids (8 .10%, 12.68% and 6.32%), respectively. There was also good sensory acceptance for the products developed, with an average score for the overall impression of 7.80, 7.32 and 7.15 for the cake, cookie and bread, respectively. Therefore, whole peach palm flour can partially replace traditional flours in cake, biscuit and bread formulations, both domestically and industrially, offering an increase in the nutritional value of final products.